História das ideias na ciência: horizontes de uma pesquisa historiográfica - Deborah Cristine Silva Gomes (2014)
The present work can be defined as a methodological exercise and its inspirations is to bring closer together history of sciences and theory of history. The chosen approach to promote this encounter was a review of the so called history of scientific ideas through the conciliation between the methodology of the history of concepts, idealized by Reinhart Koselleck, and the most recent researches in the field of the meta-scientific studies. Through this review we intend to point out a new path to the history of scientific ideas research.